2015
DOI: 10.12659/msm.895233
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Single-Nucleotide Polymorphism (SNP) in miR-146a, miR-196a2, and miR-499 and Risk of Ischemic Stroke: A Meta-Analysis

Abstract: BackgroundThe association between 3 well known SNPs – miR-146a C/G (rs2910164), miR-196a2 T/C (rs11614913), and miR-499 A/G (rs3746444) – in pre-miRNA sequences and ischemic stroke (IS) are still conflicting and inconclusive. This meta-analysis aimed to pool previous studies get a more precise assessment of the association between these 3 SNPs and the risk of IS.Material/MethodsRelevant studies were searched in online databases. The strength of the association between the SNPs and IS were estimated by pooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…These results provide evidence that plasma miR-34a-5p could be a potential biomarker in early ischemic diagnosis. Theoretically, miRNAs exist in various types of body fluids and it is not only limited to tissues [ 23 , 24 ]. Previous studies also confirmed that miRNA levels in blood are reproducible and are thus indicative of the disease state [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results provide evidence that plasma miR-34a-5p could be a potential biomarker in early ischemic diagnosis. Theoretically, miRNAs exist in various types of body fluids and it is not only limited to tissues [ 23 , 24 ]. Previous studies also confirmed that miRNA levels in blood are reproducible and are thus indicative of the disease state [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another research indicate that miR-146a expression levels were lower in lung cancer cells and could regulate COX-2 expression involved in the development of a metastatic condition (38). A functional mutation in miR-146a rs2910164 may act as a useful molecular marker for cardiovascular disease (39,40), and also for various cancer types (19,41,42). For Korean population rs2910164 may contribute to genetic susceptibility to lung cancer (43), it also can be used as a prognostic marker for NSCLC patients with surgically resected at early-stage in Chinese people (44) and another study revealed that rs2910164 CG genotype group had a higher risk of NSCLC than GG genotype group (45).…”
Section: Discussionmentioning
confidence: 99%
“…A single miRNA could bind to hundreds of mRNA targets, and these targets could be implicated in the regulation of various biological and pathological processes [810]. In previous studies, miRNA-146A, miRNA-196A2, and miRNA-499A have been involved in regulating thrombosis or inflammation pathways in the circulation system [1113]. Indeed, miRNA-146A, miRNA-196A2, and miRNA-499A in mature miRNA regions have been shown to regulate tumor necrosis factor- α , Annexin A1, and C-reactive protein [1214].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of single-nucleotide polymorphisms (SNPs) in miRNAs could affect the maturation process or target selection of miRNAs [16, 17], thus influencing the risk and/or prognosis of diseases. In particular, rs2910164 in miRNA-146A, rs11614913 in miRNA-196A2, and rs3746444 in miRNA-499A have been extensively studied in the inflammatory or vascular diseases as candidate SNPs [11, 12]. Thereby, these SNPs have been also expected to affect the risk and pathogenesis of IS.…”
Section: Introductionmentioning
confidence: 99%